Improving Islamic Education Learning Outcomes Through Problem Based Learning Model at SLB Asih Putra Padang Panjang - Wahyuni, Sri Nusa (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve Islamic education learning in Islamic religious education learning by using the problem-based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of special schools. The data of this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the problem-based learning model can improve Islamic education learning in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 45.71%, the first cycle 49.39% and in the second cycle it increased to 79.16%. Thus, the use of videos can be used as an alternative to improve student learning outcomes in Islamic religious education learning.